2020
DOI: 10.1111/jorc.12325
|View full text |Cite
|
Sign up to set email alerts
|

Innovative education for people with chronic kidney disease: an evaluation study

Abstract: SUMMARY Background An innovative Community Kidney Service has been running since 2016 in four health regions in East London, United Kingdom. This paper focuses on the patient education (self‐management) programme within the service. Objective To understand the experiences of people with stage 1–3b chronic kidney disease invited to individual or group education sessions. To assess the usefulness of the programme's educational resources to primary care nurses. Design A mixed‐method project. A steering group invo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…Innovative educational interventions to improve self‐management in patients suffering from chronic diseases have been highlighted in recent years (NHS England, 2019). This also applies to patients suffering from chronic kidney disease, and several studies have concluded the importance to support the patients to effectively manage their health challenges (Lopez‐Vargas et al, 2016; Rainey et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Innovative educational interventions to improve self‐management in patients suffering from chronic diseases have been highlighted in recent years (NHS England, 2019). This also applies to patients suffering from chronic kidney disease, and several studies have concluded the importance to support the patients to effectively manage their health challenges (Lopez‐Vargas et al, 2016; Rainey et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Such changes, however, created a significant difference of only 52% in the self‐management domain, specifically in the knowledge level, which suggests that the administered self‐management training is effective in terms of raising knowledge levels. Literature has reported an increased level of disease knowledge in adolescents with chronic diseases who undergo training (Joboshi & Oka, 2017; Lin et al, 2012; Rainey et al, 2020; Welch et al, 2014). The analysis of the behavioural changes of the adolescents based on the self‐management assessment revealed changes in such domains as blood pressure monitoring, planning health‐improvement activities, the ability to make future‐oriented planning, and the ability to request information on the tests administered at follow‐up visits.…”
Section: Discussionmentioning
confidence: 99%
“…The analysis of the behavioural changes of the adolescents based on the self‐management assessment revealed changes in such domains as blood pressure monitoring, planning health‐improvement activities, the ability to make future‐oriented planning, and the ability to request information on the tests administered at follow‐up visits. A recent paper by Rainey et al (2020) concluded that patients should be trained and given continuous support if they are to develop self‐management skills. The present study provided adolescents with supportive information on self‐monitoring, effective coping mechanisms, and what to do in stressful circumstances related to their kidney disease as part of the self‐management training, which contributed to the positive change.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation